PERAN REGULASI PEMERINTAH, DAN INOVASI EKOLOGIS DALAM MENINGKATKAN KINERJA LINGKUNGAN PADA UMKM SEKTOR MAKANAN DAN MINUMAN DI KABUPATEN KARAWANG - Taqiyah, Layinatut; Yanti, Yanti; Rachpriliani, Awaliawati (Jurnal Riset Akuntansi Politala, 2025)
MSMEs play a vital part in the country's economy, but because of the waste they generate, they also contribute to environmental contamination. The purpose of this study is to examine how ecological innovation and governmental regulation might enhance the environmental performance of MSMEs in Karawang Regency's food and beverage industry.  This study employed a quantitative approach using a descriptive methodology.  A Google Form-based survey using a Likert scale (1–5) was used to collect data. Owners and managers of MSMEs in the food and beverage industry made up the research sample, which was chosen using the purposive sampling technique.  The findings demonstrated that environmental performance is positively and significantly impacted by government regulations, suggesting that the policies in place can promote more ecologically friendly corporate activities.  Furthermore, ecological innovation has a favorable and noteworthy impact on environmental performance, suggesting that the implementation of sustainable innovation might enhance sustainability and business efficiency.  This result suggests the significance of government policies and MSME actors' innovations working together to enhance environmental sustainability.